How do the vectors of scientific credibility reconfigure at the interface between the social worlds? - Fabrizio Li Vigni; Séverine Louvel; Benjamin Raimbault (Revue d'anthropologie des connaissances)
The credibility of scientists is currently debated, especially regarding the credibility risks that may result from researchers' loss of autonomy vis-à-vis economic interests, activist rationale or political agendas. Such situations, where the credibility of scientists is put to the test in the eyes of society and their peers, raise a more general question: how do the scientists who are active in collectives situated in several social worlds build their credibility in the eyes of their colleagues? Do their activities reinforce, or weaken, the classical vectors of scientific credibility? Are new vectors of credibility emerging at the same time? The five articles in this special issue examine the contemporary reconfigurations of credibility based on four dimensions of transformation of the sciences: the rise of open data; science-industry relations; interdisciplinarity; and the public commitments of researchers. In this introductory article, we review the history of the notion of scientific credibility in Science & Technology Studies - as proposed by Bruno Latour and Steve Woolgar, then Steven Shapin and Thomas Gieryn - and the way it has been applied since then. Subsequently, we present the articles of the issue and draw transversal conclusions from them. We argue that, more than the advent of new vectors of scientific credibility, the articles show transformations at the margin, situational and contradictory.